Does Reconsolidation Occur in Humans? - Schiller, Daniela; Phelps, Elizabeth A. (Frontiers in Behavioral Neuroscience, 2011)
Evidence for reconsolidation in non-human animals has accumulated rapidly in the last decade, providing compelling` demonstration for this phenomenon across species and memory paradigms. In vast contrast, scant evidence exists for human reconsolidation to date. A major reason for this discrepancy is the invasive nature of current techniques used to investigate reconsolidation, which are difficult to apply in humans. Pharmacological blockade of reconsolidation, for example, has been typically used in animals as a proof of concept. However, most compounds used in these studies are toxic for humans, and those compounds that are safe target related, but not direct mechanisms of reconsolidation. Thus, although human reconsolidation has been hypothesized, there is limited evidence it actually exists, with the best evidence emerging from non-invasive techniques that ‘update’ memory during reconsolidation rather than block it, a technique only rarely used in animal research. Here we discuss the current state of human reconsolidation and the challenges ahead. We review findings on reconsolidation of emotional associative, episodic and procedural memories, using invasive and non-invasive techniques. We discuss the possible interpretation of these results, attempt to reconcile some inconsistencies, and suggest a conceptual framework for future research.